Exploring normativity in disability studies. Issue 1 (2nd January 2016) - Vehmas, Simo; Watson, Nick
Abstract: Normativity is a concept that is often misapplied in disability studies, especially in 'postconventional' accounts, where the concept is conflated with 'normal', 'normate', or 'standard'. This article addresses this confusion, explores the meaning and use of 'normativity', and presents some analytic tools to discuss normative issues of right and wrong. The article finishes by discussing examples where conceptual confusions result in confused normative judgments focusing in particular on agency, responsibility and moral status. The article argues that disability research should carefully consider the use of theories and empirical knowledge in the light of their ethical implications as well as the lived experiences of disability.